(untitled) (International Seven Journal of Multidisciplinary, 2025)
Drought causes morphological changes in corn, especially during the initial phase of its development. This study aimed to evaluate the sensitivity of different maize hybrids to water stress, using the Crop Water Stress Index (IEHC) and infrared thermometer to monitor the water status of plants in the early stages of development. The maize cultivars B2620 PWU, AG8701 PRO 4, P3808 VYHR and DKB360 PRO 3 were tested, submitted to a randomized block design (DBC), in a 4 x 2 x 5 factorial scheme, with 4 replications. The study considered 4 corn hybrids, 2 levels of water replacement (100% and 50% of crop evapotranspiration) and 5 evaluation times (15, 22, 29, 36 and 43 days after emergence - DAE). The lower (LBL) and upper (UBL) baselines for the IEHC calculation were determined by the lowest and highest air temperatures recorded throughout the crop cycle. The data were submitted to analysis of variance and, when significant, the qualitative data were analyzed by Tukey’s test at p<0.05 and the quantitative data by multiple regression. The results indicated that the hybrid DKB360 PRO 3 presented the lowest water stress index, demonstrating greater resistance to water scarcity. In contrast, the hybrid P3808 VYHR was more sensitive to water stress, with larger leaf area. The highest intensity of water stress was observed at 22 days after emergence, which reinforced the importance of leaf architecture in the adaptation of plants to water stress and its influence on survival during periods of drought. The water stress index of the crop should be used with weight in the choice of resistant varieties, being better indicated for monitoring the water status of the plant.